Building Deformation Prediction Based on Ground Surface Settlements of Metro-Station Deep Excavation - Dapeng Li; Changhong Yan (Advances in Civil Engineering)
Building deformations are not only closely related to the distance from the building to metro-station excavation but also related to the relative positions of the building and metro-station excavation. Building deformations can be predicted using ground surface settlement profiles. Based on typical geological parameters of Nanjing metro-station excavation, ground surface settlements were numerically simulated by auxiliary planes perpendicular and parallel to the excavation and by angled auxiliary planes at the excavation corner. Results show that the ground surface settlement profiles in auxiliary planes are closely related to the relative positions of the auxiliary planes and the metro-station excavation. Partitioning of ground surface settlements was proposed according to the three types of ground surface settlement profiles; furthermore, bending deformation and torsional deformation regularities of surrounding buildings were analyzed, and an estimation method for building settlements was developed. Finally, field-monitored settlement data of 21 buildings in different zones were compared with the estimated settlement data, and the application of the settlement estimation method to different types of foundations was analyzed. The results of this study can serve as reference for metro-station deep excavation construction and protection of surrounding buildings.